Pendampingan Pendampingan Membaca dan Menulis Aksara Jawa di Madrasah Baitus Solihin Kajor Wetan Selopamioro Imogiri Bantul: - - Suwardiyono, Dian Nugroho (Jurusan Ilmu Pendidikan - Universitas Lampung, 2023)
Kajor Wetan Village is an area that has a lot of Javanese art. There is a lot of cultural art here that continues to be preserved. One of the most basic things in culture is language. Java has its own unique script or letters, namely the Javanese script. Currently, many children are reluctant to learn about Javanese script. This is due to a lack of interest in learning Javanese script, this is of course a problem. Baitus Solihin Madrasah is the only madrasah in Kajor Wetan village. This madrasah is a gathering place for children in Kajor Wetan village. The assistance activity for reading and writing Javanese script aims to provide madrasah students with an understanding of local culture to strengthen religious teaching values and add cultural values in Kajor Wetan. This mentoring activity is divided into 3 parts over 2 days. The first day contains an explanation of the basics of Javanese script and practice reading Javanese script. The second day was filled with learning games and competitions in reading Javanese characters. In general, this mentoring activity has provided additional knowledge to madrasah students regarding Javanese script and has been able to add value to Kajor Wetan village as an arts village. Key Word: Local culture, Javanese Alphabet, Reading and Writing, Cultural Vilage